2010
DOI: 10.1007/s12098-010-0314-8
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Sepsis in a Tertiary Care Hospital in South India: Bacteriological Profile and Antibiotic Sensitivity Pattern

Abstract: Klebsiella pneumoniae was the most common agent causing both early-onset and late-onset sepsis and significantly associated with sepsis in inborn babies. Amikacin should be used along with the third-generation cephalosporins for empirical treatment of gram-negative neonatal sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
75
3
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 11 publications
17
75
3
7
Order By: Relevance
“…The prevalence of A. baumannii bacteremia in neonates has been reported to be 0.2%-6.9% [2][3][4][5]. Fourteen percent of early-onset sepsis (EOS) [6] and 9% of late-onset sepsis (LOS) in newborns has been reported to be due to A. baumannii species [7].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of A. baumannii bacteremia in neonates has been reported to be 0.2%-6.9% [2][3][4][5]. Fourteen percent of early-onset sepsis (EOS) [6] and 9% of late-onset sepsis (LOS) in newborns has been reported to be due to A. baumannii species [7].…”
Section: Introductionmentioning
confidence: 99%
“…4,19,22 In developed countries, the predominant bacteria in EONS is group B Streptococcus; 2 in our study; it was isolated in three occasions.…”
Section: Discussionmentioning
confidence: 49%
“…Such interventions may be of little access or nonexistent in low-resource countries, thus favoring a different epidemiological scene. 4,8,9 Viswanathan, et al identified that 71.7% of Gram-negative bacteria, while 81.8% were E S B L p r o d u c e r s . 10 I n o u r s t u d y , 4 0 % o f Enterobacteriaceae isolated from LONS cases were ESBL producers (n: 30), while only 6.5% of Enterobacteriaceae isolated from EONS corresponded to this type (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations